A triple‐blind, randomized controlled trial, comparing combined letrozole and clomiphene versus only letrozole for ovulation induction in women with polycystic ovarian syndrome. Issue 1 (8th October 2022) - Panda, Soumya Ranjan; Sharmila, Vijayan; Kalidoss, Vinoth Kumar; Hota, Smrutismita
Abstract: Objective: To evaluate the efficacy of combination treatment of letrozole and clomiphene citrate (CC) in comparison to that of letrozole alone to induce ovulation in infertile women with polycystic ovary syndrome (PCOS). Methods: The current study was designed as a single‐center, double‐arm and triple‐blind, randomized, controlled trial. The study was prospectively registered with the clinical trials registry in India and was conducted after approval from the institutional ethics committee. Study patients were randomly assigned to treatment with either a combination of 2.5 mg of letrozole and placebo ( n = 40) or a combination of 2.5 mg of letrozole and 50 mg of CC ( n = 40) starting from cycle days 3 to 7 for a single treatment cycle. Results: Ovulation induction with combined letrozole and CC provided a higher ovulation rate, with a 35% absolute difference in its favor. The authors found an ovulation rate of 73% versus 38% ( P = 0.003) for treatment with a combination drug and letrozole alone, respectively, while the ovulation rate ratio was 1.93 (95% CI, 1.24–3.01). Conclusion: Combined treatment of letrozole and clomiphene may be considered as one of the first‐line ovulation induction agents for infertile women with PCOS because of its affordability and better safety profile. Synopsis: Combination therapy with letrozole and clomiphene offers superior ovulation rates in infertile patients with polycystic ovary syndrome and can be considered a first‐line agent for ovulation induction.